Structuring of larval fish assemblages along a coastal-oceanic gradient in the macro-tidal, tropical Eastern Indian Ocean. (March 2019) - Beckley, L.E.; Holliday, D.; Sutton, A.L.; Weller, E.; Olivar, M.P.; Thompson, P.A.
Abstract: In the eastern Indian Ocean, the Kimberley region off north-western Australia is characterised by a wide continental shelf, complex coastal topography and very large tides (>10 m). Diversity of fishes is high although little is known about the distribution of their larvae in this dynamic region. This study investigated spatial variation in ichthyoplankton assemblages along four coastal-oceanic transects and related the results to tidal cycles and other environmental variables. Larvae representing 92 neritic and 21 mesopelagic teleost families were collected; this far exceeds the diversity described for other comparable tropical continental shelf and oceanic systems. Distinct ichthyoplankton assemblages characterised inner shelf (Engraulidae and Gobiidae were dominant families), outer shelf / slope (mixed neritic and mesopelagic taxa) and oceanic waters (mesopelagic taxa, particularly Myctophidae, Gonostomatidae and Phosichthyidae), and were correlated with changes in environmental variables (water depth, seawater density, mixed layer depth and zooplankton). The spring-neap tidal cycle and subsequent tides (same stations sampled 12 h apart) had no significant influence on larval fish assemblages. Coastal waters were delineated by a density front and larval fish assemblages were significantly different from offshore assemblages. This study provides new insights into the pelagic ecosystem in the tropical eastern Indian Ocean and contributes to the understanding of the role of environmental variables and physical forcing in the structuring of larval fish assemblages.